Access to 2‐Arylindoles via Decarboxylative C−C Coupling in Aqueous Medium and to Heteroaryl Carboxylates under Base‐Free Conditions using Diaryliodonium Salts. Issue 23 (7th November 2016) - Arun, Velladurai; Pilania, Meenakshi; Kumar, Dalip
Abstract: Easily accessible heteroaromatic carboxylic acids and diaryliodonium salts were successfully employed to construct valuable 2‐arylindoles and heteroaryl carboxylates in a regioselective fashion. C2‐arylated indoles were produced using a Pd‐catalyzed decarboxylative strategy in water without any base, oxidant, or ligand. Heteroaryl carboxylates were prepared under metal and base‐free conditions. This protocol was successfully utilized to synthesize Paullone, a cyclin‐dependent kinase (CDK) inhibitor. Abstract : Two birds, one stone : Diaryliodonium salts have been successfully employed to construct 2‐arylindoles and heteroaryl carboxylates. The indoles are prepared using decarboxylative C−C coupling strategy in water. The carboxylates are produced under base‐free conditions.